Mengenal Lebih Dalam Pendidikan Kewarganegaraan Hingga Jenjang Perguruan Tinggi - Tsabitah Rafifah; Dinie Anggraeni Dewi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of writing this article is to inform readers so that they can better understand the subjects of Citizenship Education. Because this lesson is very useful to build ourselves into a good citizen about citizenship.Citizenship Education (Civics) is one of the existing subjects from elementary school to tertiary education. The mission of Citizenship Education itself is to educate the nation's life. The word for citizenship in Latin is called Civicus. Furthermore, the word Civicus is absorbed into English to become the word Civic which means citizen or citizenship. From the word Civic, the word Civic was born, namely citizenship science, and Civic Education, namely Civic Education. Civics or citizenship lessons have been known in Indonesia since the Dutch colonial era under the name Burgerkunde.